Perfect Worlds Utopian Fiction in China and the West - Fokkema, Douwe (Amsterdam University Press, 2011)
Perfect Worlds offers an extensive historical analysis of utopian narratives in the Chinese and Euro-American traditions. This comparative study discusses finally the rise of dystopian writing - a negative expression of the utopian impulse - in Europe and America (Zamyatin, Huxley, Orwell, Bradbury, Atwood) as well as in China (Lao She, Wang Shuo, and others). The author observes that the utopian imagination thrives in a context of secularization. It appears that in the twentieth century the distinction between utopia and dystopia is blurred as a result of the increasing autonomy of the reader. Fokkema argues that in modern times utopianism in China and in the West has developed in opposite directions, each appropriating attitudes from the other culture which originally were considered alien.